RFID Technology as a Promising Support in Logistic Information Systems - Wilk, Krzysztof (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2008)
The article concentrates on information technologies supporting logistics. In the information society, in which knowledge possessing is the main source of wealth, companies in order to meet client needs have to adapt to constantly improving IT solutions. Logistic information systems allow the cooperation among producers, deliverers, distribution centers and clients. This cooperation needs each participant of the supply chain to communicate. Automatic identification of data improves this communication. One of the most promising solutions within logistic information systems of automatic identification is RFID technology. Its functioning and advantages surpassing bar codes are characterized in the article.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 25, s. 152-162